DAMPAK PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP PEMAHAMAN KONSEP PADA SISWA SEKOLAH DASAR - Azrina Ratna Masriani; Haifaturrahmah; Yuni Mariyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of information technology has brought profound transformations to the field of education, particularly in elementary schools. Learning in the digital era requires continuous innovation to ensure that teaching practices remain relevant and effective. Elementary schools play a crucial role in preparing students to adapt to technological developments by integrating digital tools into classroom activities. Teachers are now expected to utilize technology to create learning experiences that are more interactive, engaging, and meaningful. This study aims to analyze the impact of technology-based learning media on students’ conceptual understanding in elementary education. The research adopts a descriptive analytical approach through a comprehensive review of relevant studies and theoretical frameworks concerning technology integration in learning. The results show that digital learning media significantly improve students’ motivation, participation, and comprehension of abstract concepts. Visual and interactive media—such as educational applications, animations, and digital simulations—enable students to connect prior knowledge with new information, fostering deeper conceptual understanding. Nevertheless, several challenges remain, including limited infrastructure, lack of teacher readiness, and the persistence of conventional teaching methods in many schools. Addressing these challenges requires systematic efforts to strengthen teachers’ digital literacy, provide adequate facilities, and design creative, student-centered learning media. The findings of this study are expected to contribute theoretically to the discourse on technology integration in primary education and practically to guide teachers in implementing effective digital-based learning strategies. In